2021
DOI: 10.3390/brainsci12010042
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Low-Frequency Oscillations in fNIRS as Cerebral Response to Auditory Stimulation with Familiar Music

Abstract: Recognition of typical patterns of brain response to external stimuli using near-infrared spectroscopy (fNIRS) may become a gateway to detecting covert consciousness in clinically unresponsive patients. This is the first fNIRS study on the cortical hemodynamic response to favorite music using a frequency domain approach. The aim of this study was to identify a possible marker of cognitive response in healthy subjects by investigating variations in the oscillatory signal of fNIRS in the spectral regions of low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Moreover, music-based interventions are already employed in patients with disorders of consciousness and are thought to have a beneficial effect during neurorehabilitation by increasing neuroplasticity (Sihvonen et al, 2017, Verger et al, 2014. In a previous study with healthy subjects, we found an increase of spectral power of low-frequency oscillation (LFO) within HbO2signal measured by fNIRS, after exposure to preferred music, followed by a decrease in LFO spectral power after the end of music (Bicciato et al, 2021). Therefore, for the current study, hemodynamic response to music measured was defined by this pattern of change in LFO spectral power during and after music exposure.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Moreover, music-based interventions are already employed in patients with disorders of consciousness and are thought to have a beneficial effect during neurorehabilitation by increasing neuroplasticity (Sihvonen et al, 2017, Verger et al, 2014. In a previous study with healthy subjects, we found an increase of spectral power of low-frequency oscillation (LFO) within HbO2signal measured by fNIRS, after exposure to preferred music, followed by a decrease in LFO spectral power after the end of music (Bicciato et al, 2021). Therefore, for the current study, hemodynamic response to music measured was defined by this pattern of change in LFO spectral power during and after music exposure.…”
Section: Introductionmentioning
confidence: 74%
“…We compared the cohort of patients to a group of 6 healthy controls. The data of the control group has been previously published (Bicciato et al, 2021). The study was approved by the local ethics committee.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations